PENGELOLAAN SITUS CAGAR BUDAYA KOTA CINA MEDAN - Nadya Flandro Sinaga; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Management of cultural heritage is very important, considering the area of cultural heritage is an asset that must be preserved because of its historical value the history of the past that can not be updated. Medan has a cultural heritage site that China City Site of Medan. In accordance with Local Rule No. 2 of 2012 on the cultural heritage in the city of Medan, management of cultural heritage sites of cultural field is still not optimal. This is caused because the Department of Culture Tourism and still can not delude potential cultural heritage sites owned by managing well in order to remain sustainable existence and can be utilized. The purpose of this study is that the Department of Culture and Tourism of Medan is expected to in the management of cultural heritage in order to remain sustainable .Sehingga future generations can know the past glory ever etched in the city of Medan and can be used also for educational facilities, as well as the history and can impact on the economy which became the object of cultural tourism can increase Genuine Income area.In explaining the management of the heritage city of China Medan using the theory of George Terry concept of supervision. This study used a qualitative descriptive method. Data was collected through interviews, observation, documentation, and literature.The results showed that the management of the heritage city of China Medan is still not optimal. Due to supervision by the Department of Culture and tourism in the management of cultural heritage sites of china town is not maximized. So that the cultural heritage sites have less impact to the community.Key Words: Management, cultural heritage site, the department of culture and tourism